FACTORS AFFECTING PHYSICAL INVESTMENT IN ASEAN COUNTRIES - Nano Prawoto (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of economic growth, labor force, interest rate, tax revenue, trade, and industrial value added on gross fixed capital formation / PMTB in ASEAN countries with a panel data approach. The methodology used in this study is panel data regression with Fixed Effect Model approach. The data used in this study are from 2001 to 2021 in 5 ASEAN countries. The results of this study show that labor force, trade value and industrial value added have a positive influence on gross fixed capital formation, while economic growth, interest rate and tax revenue have a negative influence on gross fixed capital formation. The implication of this research is that ASEAN countries must increase the competitiveness of industrial products to increase capital inflow in the ASEAN Region.